PSYCHOLOGICAL AND GERMANAFTIC ASPECTS OF COMMUNICATION - Карпенко, З. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The subject, conditions, procedures and mechanisms of psychological and germanaftic investigation of communication have been examined in the article: valued and sensible consciousness of the personality, dialogical interaction, understanding, interpretation, explanation of behavioral acts, openness and approachability, authenticity etc.